Pengaruh Kompetensi Guru Terhadap Hasil Belajar Peserta Didik di Madrasah Ibtidaiyah - Alam, Muchammad Bachrul; Darmawan, Didit (LPPM Institut Pendidikan Nusantara Global, 2025)
This research was conducted with the aim of analyzing the influence of teacher competence on student learning outcomes at Madrasah Ibtidaiyah through the literature study method. In this study, the author collected and reviewed various related literature, including journal articles, books and previous research reports that discuss teacher competency and its impact on learning. The results of the analysis show that teacher competency in the fields of pedagogy, personality, professionalism and social play an important role in improving student learning achievement. Highly skilled teachers usually create a supportive learning environment, increase student engagement, and implement efficient teaching methods. These findings indicate that it is necessary to increase teacher competency through training and professional development in order to improve learning outcomes at Madrasah Ibtidaiyah. It is hoped that this research will provide valuable insight for policy makers in efforts to improve the quality of education.